2006
DOI: 10.1145/1132863.1132865
|View full text |Cite
|
Sign up to set email alerts
|

Topological relationships between complex spatial objects

Abstract: For a long time topological relationships between spatial objects have been a focus of research in a number of disciplines like artificial intelligence, cognitive science, linguistics, robotics, and spatial reasoning. Especially as predicates they support the design of suitable query languages for spatial data retrieval and analysis in spatial databases and geographical information systems (GIS). Unfortunately, they have so far only been defined for and applicable to simplified abstractions of spatial objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 27 publications
2
199
0
4
Order By: Relevance
“…Several research approaches have shown that the granularity of formal calculi is inadequate for modeling human conceptualizations of both static and dynamic spatial relations. To address this issue the majority of approaches (e.g., Clementini, Di Felice, & van Oosterom, 1993;Schneider & Behr, 2006) define formal criteria on how to cluster topological equivalence classes such that the overall number of topological predicates is reduced. Clementini and collaborators (1993) suggest five basic relations that are derived on the basis of the emptiness and non-emptiness of component intersection, inclusion and non-inclusion of one object in another object, and the dimension of the component intersection.…”
Section: Discussionmentioning
confidence: 99%
“…Several research approaches have shown that the granularity of formal calculi is inadequate for modeling human conceptualizations of both static and dynamic spatial relations. To address this issue the majority of approaches (e.g., Clementini, Di Felice, & van Oosterom, 1993;Schneider & Behr, 2006) define formal criteria on how to cluster topological equivalence classes such that the overall number of topological predicates is reduced. Clementini and collaborators (1993) suggest five basic relations that are derived on the basis of the emptiness and non-emptiness of component intersection, inclusion and non-inclusion of one object in another object, and the dimension of the component intersection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Open GIS Consortium also provides a Reference Model [45] as a standard for a representing geo-spatial information. Qualitative spatial operations include topological relations [46] such as disjoint, meet, overlap, equal, inside, contains, covers and coveredBy, and cardinal direction relations. Quantitative relations on spatial objects include metric operations based on the size, shape and metric distances between objects or their components.…”
Section: Related Workmentioning
confidence: 99%
“…Fuzzy set theory [10] has been a popular approach to modeling vague spatial objects and resulted in a concept of fuzzy regions [5,8]. A crisp region object is conceptually modeled as a particular point set of the Euclidean plane [7,9]. Each of its points belongs definitely and completely to it.…”
Section: Fuzzy Regionsmentioning
confidence: 99%
“…. , r 9 and their associated membership values. All membership values are different, and any pair of crisp regions is either disjoint (e.g., r 1 and r 9 ) or adjacent (e.g., r 2 and r 5 ).…”
Section: Plateau Regions As a Representation Of Fuzzy Regionsmentioning
confidence: 99%
See 1 more Smart Citation